Language loyalty to the ethnic language among the Hausa community in Khartoum - Muhammad N. Osman (Этническая культура, 2025)
This article presents the results of a comprehensive study of the language loyalty of Hausa speakers in the urban environment of Khartoum. Based on field data collected in 2022–2025 (one hundred in-depth interviews and questionnaires), the key factors influencing the preservation of the ethnic language in the diaspora community are analyzed. Particular attention is paid to the intergenerational dynamics of language preferences, strategies of language socialization, and the role of language attitudes in identification processes. An analysis of language loyalty in the Hausa diaspora environment showed that, in addition to the traditional criterion of recognizing an ethnic language as native, important indicators include practices of preserving cultural heritage. In the Khartoum diaspora, a special role is played by maintaining song traditions and watching foreign films in the Hausa language, and regular meetings of community representatives. For most respondents, the native language performs a predominantly symbolic function, serving as a marker of group identity and a bearer of cultural values. In general, the results demonstrate a complex picture of language shift, where the traditional “home-street-school” triad undergoes significant transformations under the influence of urbanization processes. The study makes a significant contribution to understanding the mechanisms of language stability in the context of Arabic-African language contact.